Structure, Functions, and Physiological Roles of the Lipocalin α1-Microglobulin (A1M) - Bergwik, Jesper; Kristiansson, Amanda; Allhorn, Maria; Gram, Magnus; Åkerström, Bo (Frontiers in Physiology, 2021)
α1-microglobulin (A1M) is found in all vertebrates including humans. A1M was, together with retinol-binding protein and β-lactoglobulin, one of the three original lipocalins when the family first was proposed in 1985. A1M is described as an antioxidant and tissue cleaning protein with reductase, heme- and radical-binding activities. These biochemical properties are driven by a strongly electronegative surface-exposed thiol group, C34, on loop 1 of the open end of the lipocalin barrel. A1M has been shown to have protective effects in vitro and in vivo in cell-, organ- and animal models of oxidative stress-related medical conditions. The gene coding for A1M is unique among lipocalins since it is flanked downstream by four exons coding for another non-lipocalin protein, bikunin, and is consequently named AMBP, α1-microglobulin-bikunin precursor gene. The precursor is cleaved in the Golgi, and A1M and bikunin are secreted from the cell separately. Recent publications have suggested novel physiological roles of A1M in regulation of endoplasmic reticulum activities and erythrocyte homeostasis. This review summarizes the present knowledge of the structure and functions of the lipocalin A1M and presents a current model of its biological role(s).